Decoupling of optical and electrical properties of rear contact CIGS solar cells - Cunha, J. M. V. (2019)
A novel architecture that comprises rear interface passivation and increased rear optical reflection is presented with the following advantages: i) an enhanced optical reflection is achieved by depositing a metallic layer over the Mo rear contact; ii) the addition of a sputtered Al2O3 layer improves the interface quality with CIGS; and, iii) the rear-openings are refilled with Mo to maintain the optimal ohmic electrical contact as generally observed from the growth of CIGS on Mo. Hence, a decoupling between the electrical function and the optical function of the substrate is achieved. We present in detail the manufacturing procedure of such type of architectures together with its benefits and caveats. A preliminary electrical analysis of resulting solar cells showing a proof-of-concept of the architecture is presented and discussed.